2014
DOI: 10.4161/15384101.2014.947786
|View full text |Cite
|
Sign up to set email alerts
|

γH2AX foci on apparently intact mitotic chromosomes: Not signatures of misrejoining events but signals of unresolved DNA damage

Abstract: Abbreviations: AU, arbitrary units; DSB, DNA double-strand break; FISH, fluorescence in situ hybridization; IRIF, ionizing radiation induced foci; FI, fluorescence intensity; mFISH, multicolor fluorescence in situ hybridization; MRN complex, MRE11-Rad50-Nbs1 complex; SD, standard deviation; TIF, telomere-dysfunction induced foci.The presence of gH2AX foci on apparently intact mitotic chromosomes is controversial because they challenge the assumed relationship between gH2AX foci and DNA double-strand breaks (DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Thus if these incomplete chromosome elements are able to reach cytokinesis, they should be transmitted to daughter cells, as were the persistent IRIF observed in our study. Analyzing metaphase cells, Martin et al reported that persistent IRIF do not seem to co-locate with either telomere-free chromosome ends or misrepaired breaks [41]. It is nonetheless important to note that histone H2AX phosphorylation takes place on serine 139 along the chromosome arms from metaphase to telophase, independently of any DNA damage induced [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Thus if these incomplete chromosome elements are able to reach cytokinesis, they should be transmitted to daughter cells, as were the persistent IRIF observed in our study. Analyzing metaphase cells, Martin et al reported that persistent IRIF do not seem to co-locate with either telomere-free chromosome ends or misrepaired breaks [41]. It is nonetheless important to note that histone H2AX phosphorylation takes place on serine 139 along the chromosome arms from metaphase to telophase, independently of any DNA damage induced [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…as pointed out recently [285,288], in some conditions, they may also be indicative for unresolved DNA damage that may promote cellular senescence.…”
Section: Biomarkers Relevant For Radiation Dosimetry and Biological Amentioning
confidence: 76%
“…HR is activated and works during the S and G2 phases of the cell cycle [ 33 ]. Martin et al showed MRE11 is induced in response to DNA injury and co-localized with γH2AX after irradiation, measured by IF in lymphoblastoid cell lines in vitro [ 34 ]. Choudhry and colleagues examined protein expression of MRE11, RAD50, NBS1, ATM, and H2AX by immunohistochemistry in pretreatment tumor specimens from 179 bladder cancer patients receiving radical radiotherapy.…”
Section: Discussionmentioning
confidence: 99%